Optimized frequency dependent photothermal beam deflection spectroscopy. (4th November 2016) - Korte, D; Cabrera, H; Toro, J; Grima, P; Leal, C; Villabona, A; Franko, M
Abstract: In the letter the optimization of the experimental setup for photothermal beam deflection spectroscopy is performed by analyzing the influence of its geometrical parameters (detector and sample position, probe beam radius and its waist position etc) on the detected signal. Furthermore, the effects of the fluid's thermo-optical properties, for optimized geometrical configuration, on the measurement sensitivity and uncertainty determination of sample thermal properties is also studied. The examined sample is a recently developed CuFeInTe3 material. It is seen from the obtained results, that it is a complex problem to choose the proper geometrical configuration as well as sensing fluid to enhance the sensitivity of the method. A signal enhancement is observed at low modulation frequencies by placing the sample in acetonitrile (ACN), while at high modulation frequencies the sensitivity is higher for measurements made in air. For both, detection in air and acetonitrile the determination of CuFeInTe3 thermal properties is performed. The determined values of thermal diffusivity and thermal conductivity are (0.048 ± 0.002) × 10 −4 m 2 s −1 and 4.6 ± 0.2 W m −1 K −1 and (0.056 ± 0.005) × 10 −4 m 2 s −1 and 4.8 ± 0.4 W m −1 K −1 for ACN and air, respectively. It is seen, that the determined values agree well within the range of their measurement uncertainties for both cases, although the measurement uncertainty is two times lower for the measurements in ACN providing more accurate results. The analysis is performed by the use of recently developed theoretical description based on the complex geometrical optics. It is also shown, how the presented work fits into the current status of photothermal beam deflection spectroscopy.